Osteoporosis across chronic liver disease. Issue 6 (June 2016) - Guarino, M.; Loperto, I.; Camera, S.; Cossiga, V.; Somma, C.; Colao, A.; Caporaso, N.; Morisco, F.
Abstract Osteoporosis is a complication of chronic liver disease, with impact on morbidity, quality of life, and survival. The progress of medicine and the new therapies stretched the disease's natural history and improved the survival of patients with liver disease. So, it is fundamental to make better the quality of life and to prevent complications. Metabolic bone disorders are common complications of chronic liver disease (CLD). Patients with CLD have an increased risk of bone fractures, with significant impact on morbidity, quality of life, and even on survival. Bone diseases, including osteomalacia, osteoporosis, and osteopenia, are frequently observed in many types of liver disease. The pathogenesis of damage and the mechanisms of bone loss are different in relation to the specific liver disease. The relevance of these conditions induced many authors to create a new nosographic entity known as "hepatic osteodystrophy", although this term is rarely used anymore and it is now commonly referred to as osteopenia or osteoporosis associated with chronic liver disease. This review is based on the personal experiences of the authors and upon research done of the available literature on this subject matter. The authors searched the PubMed database for publications containing the term "liver disease" in combination with "bone disease", "hepatic osteodistrophy", "osteoporosis", "osteopenia", "osteomalacia", and "fractures". They selected publications from the past 10 years but did not exclude older seminal publications, especially for colestatic liver diseases. This review of literature shows that osteoporosis crosses all CLD. It is important to underline that the progress of medicine and the new therapies stretched the disease's natural history and improved the survival of patients with CLD. It is fundamental to make better the quality of life and it is mandatory to prevent complications and in particular the osteoporotic ones, especially fractures.